Penerapan Sistem Pengendalian Manajemen pada Tim Bola Basket ITHB Arrows - Richard Theofilus Hartanto; Boby Wiryawan Saputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the implementation of Management Control Systems (MCS) in the ITHB Arrows basketball team to achieve the team’s vision and mission while enhancing athlete motivation and performance. Key elements identified include structured training programs, performance evaluations, and motivation's role. Despite resource limitations, the findings suggest significant contributions of effective MCS practices to performance optimization. Recommendations include improved facilities and mission internalization for future strategy. Moreover, this study provides a comprehensive analysis of behavioral and motivational factors influencing success. By benchmarking against competitive teams, best practices are identified for long-term sustainable performance.